Clinical significance of soluble Fas plasma levels in patients with sepsis - Mikić, Dragan; Vasilijić, Saša; Ćućuz, Milica; Čolić, Miodrag (Vojnosanitetski pregled, 2015)
Background/Aim. The goal of modern clinical and experimental researches in the field of sepsis is to find one or more sensitive parameters that could predict the severity of sepsis and its outcome. In this study we investigated and compared the relationship of initial soluble Fas (sFas) plasma levels as well as Acute Physiology, Age and Chronic Health Evaluation II (APACHE II) score in 58 septic patients with severity and outcome of sepsis. Methods. The diagnosis and assessment of disease severity was performed on the same day, based on clinical and laboratory parameters. The blood samples were used for monitoring of laboratory standard parameters necessary for the diagnosis of sepsis, organ dysfunction and assessment of disease severity, as well as for determination of levels of sFas. According to consensus criteria, patients were divided into those with sepsis (n = 16), severe sepsis (n = 30) or septic shock (n = 12), those with (n = 26) and without (n = 32) multiple organ dysfunction syndrome (MODS), and survivors (n = 45) and non-survivors (n = 13). Results. Plasma sFas level (9.7 ± 10.1; 0–44.2 U/mL) was elevated in 54.4%  of patients. All the patients with septic shock, 76.9% of the patients with MODS and 84.6% patients who died had elevated sFas level. We observed a strong positive correlation between sFas and APACHE II score (p < 0.001). The level of sFas was significantly higher in patients with septic shock compared to normotensive patients (p < 0.001), patients with MODS compared to those without MODS (p < 0.001) and survivors compared to nonsurvivors (p < 0.01). Conclusions. Our results suggest that initial sFas plasma levels in patients with sepsis correlated with the values of APACHE II score and separated very well the patients with septic shock versus the normotensive patients, the patients with and without MODS, and survivors versus non-survivors
Keywords: sepsis; antigens; cd95; plasma; prognosis